Influence of transplant size on the above- and below-ground performance of four contrasting field-grown lettuce cultivars - Kerbiriou, Pauline J.; Stomph, Tjeerd-Jan; Lammerts Van Bueren, Edith T.; Struik, Paul C. (Frontiers in Plant Science, 2013)
Background and aims: Modern lettuce cultivars underperform under conditions of variable temporal and spatial resource availability, common in organic or low-input production systems. Information is scarce on the impact of below-ground traits on such resource acquisition and performance of field-grown lettuce; exploring genetic variation in such traits might contribute to strategies to select for cultivars robust enough to perform well in the field, even under stress. Methods: To investigate the impact of below-ground (root development and resource capture) on above-ground (shoot weight, leaf area) traits, different combinations of shoot and root growth were created using transplants of different sizes in three field experiments. Genetic variation in morphological and physiological below- and above-ground responses to different types of transplant shocks was assessed using four cultivars. Results: Transplanting over-developed seedling did not affect final yield of any of the four cultivars. Small transplant size persistently impacted growth and delayed maturity. The cultivars with overall larger root weights and rooting depth, ‘Matilda’ and ‘Pronto’, displayed a slightly higher growth rate in the linear phase leading to better yields than ‘Mariska’ which had a smaller root system and a slower linear growth despite a higher maximal exponential growth rate. ‘Nadine’, which had the highest physiological nitrogen-use efficiency (NUE, g dry matter produced per g N accumulated in the head) among the tested cultivars, gave most stable yields over seasons and locations. Conclusions: Robustness was conferred by a large root system exploring deep soil layers. More roots generally correlated with improved nitrate capture in a soil layer and cultivars with a larger root system may therefore perform better in harsh environmental conditions; increased NUE can also confer robustness at low cost for the plant, and secure stable yields under a wide range of growing conditions.